Essays on precision agriculture technology adoption and agricultural cooperative mergers - Ofori, Eric Kwesi Makafui (Kansas State University, 2022)
Understanding how differences in precision agriculture (PA) technology adoption may impact crop productivity is important for assisting farmers to make more informed adoption choices. Also, examining if strategic alliances amongst agricultural cooperatives can provide benefits to farmers is relevant. This dissertation therefore consists of three essays that provide insights into how PA technology adoption choices may improve crop productivity, and how mergers or other forms of strategic alliances amongst agricultural cooperatives can provide additional benefits to cooperative-member farms. The first study of this dissertation evaluates potential crop productivity improvements that can be attributed to adoption of PA technologies. In this study, treatment effect estimators are incorporated into a stochastic frontier analysis framework to estimate the impact of PA technology adoption on technical inefficiency of corn production. Empirical estimations utilize data from the Kansas Farm Management Association consisting of 444 farms between 2002 to 2015. This includes non-adopters and adopters of two PA technologies: precision soil sampling (PSS) and variable rate technology (VRT). The sample data is pre-processed by using propensity score matching to account for potential underlying differences between adopters and non-adopters that may have spillover effects on the outcome of interest, technical inefficiency. Results suggest that adoption of PA technologies had no statistically significant impact on reducing technical inefficiency of corn production, in the presence of some degree of covariate imbalance. In the first study, differences amongst adopters are not considered, that is whether farms adopt PSS only or both PSS and VRT. However, estimates of technical inefficiency reductions may be masked by differences in adoption choices. The results of the first study therefore inspire the second study of this dissertation. The second study, accounts for differences in PA technology adoption choices by grouping adopters as either adopters of PSS only or adopters of both PSS and VRT. The methodology and data of the first study are adapted to estimate the impact of PA technology adoption on technical inefficiency of corn production under each adoption choice. In the presence of some degree of covariate imbalance, results suggest that, regardless of adoption choice (i.e., whether farms adopt PSS only or both PSS and VRT), adoption had no statistically significant effect on reducing technical inefficiency of corn production. The third study of this dissertation examines potential gains that agricultural cooperatives may accrue from mergers. An ex-ante data envelopment analysis approach is employed. Empirical estimations utilize data from CoBank, consisting of 749 midwestern agricultural cooperative observations from 2011 to 2015. Potential overall merger effects are decomposed into learning effects, scope effects, and scale effects. Findings show that generally, there are non-trivial overall potential gains from mergers. Overall merger gains are primarily driven by improvements due to learning effects and scope effects. Scale effect on the other hand tends to work against all merger combinations, with higher associated revenue reductions (or cost increases) for mergers between larger sized cooperatives compared to mergers between smaller cooperatives.
Keywords: Technology; Adoption; Efficiency; Mergers; Cooperatives